The bees of the tribe Anthidiini (Hymenoptera, Megachilidae) described by Ferdinand Morawitz from the collection of Aleksey Fedtschenko - Ivlev, Konstantin S.; Astafurova, Yulia V.; Proshchalykin, Maxim Yu. (Zootaxa, 2025)
The type specimens of the tribe Anthidiini described by Ferdinand Morawitz from the collection of Aleksey Fedtschenko deposited in the Zoological Museum of the Moscow State University and in the Zoological Institute, Russian Academy of Sciences St. Petersburg (Russia), are critically reviewed. Precise information with illustrations of types for ten taxa is provided, of these eight species are valid and two are probably synonyms. Lectotypes are here designated for Anthidium fedtschenkoi Morawitz, 1875, A. forcipatum Morawitz, 1875, and A. ruficorne Morawitz, 1875. The holotypes of Anthidium nigrinum Morawitz, 1875 and A. petechiale Morawitz, 1875 were not found and are probably lost.